PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING PADA MATERI IMPULS DAN MOMENTUM UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS X MIA MAN 1 PEKANBARU - Sri Rahma Yulia; M. Nor M. Nor; M. Rahmad M. Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research aimed to know the improvement on students’ critical thinking skills and to know the difference of students’ learning outcomes between grade X MIA 5 that learned through guided inquiry learning model and grade X MIA 3 that learned through conventional method. This research was conducted from March until August 2017. This was an quasy experimental research with nonequivalent control group design. The population of this study was all students of grade X MIA of MAN 1 Pekanbaru. The sampling method used was simple random sampling consisted of 57 students, grade X MIA 5 was randomly assigned as an experimental class consisted of 28 students and grade X MIA 3 as the control class consisted of 29 students. The data collection instrument used in this research was multiple choice questions. Based on analyze of comprehension tests, of post-test showed that the mean percentage experiment class was 63,57 % and control class was 51,72 %. Furthermore N-Gain of critical thinking skill was 0,43 on experiment class and 0,06 on control class. Based on analyze of t-test, there was a significant improvement critical thinking skills students learning outcomes between students learned through guided inquiry learning model and those who only learned through conventional method. The result of descriptive analyze and inferential analyze application of guided inquiry learning model of impulse and momentum materials can improvement critical thinking skills at grade X MIA MAN 1 Pekanbaru.Keywords: Critical thinking skills, guided inquiry learning, momentum and impulse